Synthesis and structural properties of vanadium doped zinc oxide. (October 2015) - Abaira, R.; Buffagni, E.; Matoussi, A.; Khmakhem, H.; Ferrari, C.
Highlights: Vanadium doped zinc oxide nanocrystals are prepared by the sol gel method. The XRD results have proven that all this samples had a wurtzite structure. The grain size increases as the vanadium concentration increases. We show a rough surface for all the pellets, and the surface roughness increases. Raman spectrum shows the appearance of E1 and E2 modes of all samples. Abstract: In this work, structural and morphological properties of vanadium doped zinc oxide (ZnO:V) pellets with different percentage of vanadium (2–10%) obtained by sol gel method have been investigated by X-ray diffraction, Raman spectroscopy and atomic force microscopy. XRD analysis showed that this samples are polycrystalline with a hexagonal wurtzite structure with (1 0 1) plane as the preferred orientation. The grain size of the pellets was increased with increasing concentration of vanadium. The atomic force microscopy shows a rough surface for all the pellets, we can see also that the surface roughness increases with increasing of doping concentration of 93–214 nm. Raman spectroscopy reveals a shift position in zinc oxide modes due to vanadium doping, the appearance of E1 and E2 modes showed that the wurtzite structure of ZnO is still maintained after doping of vanadium.